Thinking like a lawyer : essays on legal history and general history for John Crook on his eightieth birthday - Crook, J. A.; McKechnie, Paul, 1957- (Mnemosyne, Supplements, 2002)
This is a book about the law and life of Rome-in which contributors respond to John Crook's injunction to 'think like lawyers' by ranging as far as ancient Greece, ancient Persia and modern Denmark to expound their themes and draw comparisons. An opening section focuses on Civil Law, more or less as conventionally conceived, with chapters on the peculium, on municipal law at Irni in Roman Spain, on advisers of Roman provincial governors, and on violent crime. Roman perceptions of the physical and human worlds are the focus of a second section, and comparisons between Greek, Roman and modern ways of thinking about law and government come into the third section. In the final section, contributors argue the history of law and life from refractions of real and imagined Rome.